A conciliação como instrumento de acesso à justiça no âmbito da vara do trabalho de Caxias-Ma - SOUSA , Fábio Ribeiro (2017)
The present research is devoted to analysing the conciliation institute as a way and methodology of solving labor disputes, under the prism of the right of effective access to Justice and focusing on the results of Labor Court of Caxias (MA), in which the author acts as adjunct Judge. The study is justified in view of the urgent identification and administration of mechanisms that optimize effective and satisfactory jurisdictional rendering, and this conciliation emerges as an alternative in this universe. The research is carried out according to the deductive method, promoting a bibliographic review of the object of study, with reference to the legislation, doctrine and jurisprudence related to the subject, besides a field research carried out in the territorial space in which the research is limited. The study begins with a brief explanation of the jurisdiction, effectiveness and right of access to justice, as well as the conceptualization an characterization of the different adequate means of conflict resolution, such as arbitration, mediation an conciliation. Contextualizes the object of study. Afterwards, the conciliation institute is specifically analysed, highlighting its condition as a consensual meas of conflict resolution, addressing the evolution of the institute in Brazil in the last thirty years, as well as its objective, highlighting the pioneering work of the Labor Court in Brazil. Use of the institute through the experience of the Prior Conciliation Commissions, as well as the use of conciliation especifically in the Labor Court of Caxias (MA). Finally, ending considerations on research ar drawn up, which point out the importance of conciliation in the sense of realizing the reight of acces to effective judicial services.